Hypertension Treatment in the Ambulatory Setting: Comparison by Race and Gender in a National Survey - Bonds, Denise E. (J Clin Hypertens (Greenwich), 2007)
To determine if different therapies are used in different racial groups and by gender, data from the National Ambulatory Medical Care Survey and the National Hospital Ambulatory Care Survey (national probability samples of outpatient visits) were used. All visits for hypertension in 1999 and 2000 were reviewed. Survey weights were applied to obtain national estimates. Provision of therapies by gender and race/ethnicity (white, African American, Hispanic, Asian) was examined. Over 137 million visits for hypertension care were made during 1999 and 2000. Diet and exercise counseling were performed at a low percentage of visits (35% and 26% of visits, respectively). The most common antihypertensive agent prescribed was angiotensin‐converting enzyme inhibitors or angiotensin‐receptor blockers (28%), while first‐line drugs, diuretics (23%) and β blockers (15%), which are recommended by national committees, were prescribed less frequently. Asians and Hispanics were more likely to receive counseling on diet (Asians: odds ratio [OR], 2.29; 95% confidence interval [CI], 1.45–3.60; Hispanics: OR, 2.51; 95% CI, 1.18–5.33) and exercise (Asians: OR, 2.44; 95% CI, 1.35–4.42; Hispanics: OR, 3.28; 95% CI, 1.50–7.21) than non‐Hispanic whites. African Americans were more likely to be prescribed calcium channel blockers (OR, 1.51; 95% CI, 1.20–1.91) and diuretics (OR, 1.37; 95% CI, 1.08–1.74). Low use of recommended therapies was found. Although variation by race was seen, it did not systematically favor groups associated with poor outcomes.